Histomorphometry of regenerated tibial bone tissue in rats of different age under violation of saltwater balance - Pogorelov M.V. (Морфологія, 2010)
Formation of regenerated bone tissue in rats of different age at normal conditions and at hyperhydration has beenstudied. It was revealed the features in composition of regenerated tissue at a different stages of bone repair process that dependson rat's age. The hypoosmolar hyperhydration cause disorders of regenerated tissue development and inhibit lamellarbone tissue formation. With the help of statistical methods it was shown the dependence of the age and hyperhydration degreeon regenerated tissue composition.